Numerical research on inlet total pressure distortion in a transonic compressor with non-axisymmetric stator. (February 2019) - Sun, Peng; Fu, Wenguang; Wang, Hong; Zhong, Jingjun
The adverse impacts of non-uniform inlet flow have been the focus for several decades with the increase of the operating range of engines. A deep understanding of the flow mechanism of distortion passing through a compressor is needed urgently and the improvement of the compressor performance becomes more and more important. In this paper, a non-axisymmetric stator is presented with significant non-axisymmetric characteristics in a transonic compressor to investigate compressor performance and flow field effects. A time-dependent three-dimensional Reynolds-averaged Navier-Stokes equation composed in 'Fluent Software Pack' is validated and used to perform the simulations. The flow fields with distorted inlet are obtained and the effects of original stator and non-axisymmetric stator in a transonic compressor are compared. The results are discussed in terms of the effects of non-axisymmetric stator on compressor performance, blockage of flow passage, rotor and stator. The results show that the non-axisymmetric stator influences not only the stator flow field but also the rotor flow field, so the efficiency and total pressure ratio are improved correspondingly.